Standar Akuntansi Pemerintah, Sistem Informasi Akuntansi, dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan dengan Kompetensi Sumber Daya Manusia Sebagai Pemoderasi - Wiwiek Djumiyati; Khristina Yunita; Muhsin; Angga P. Karpriana; Rusliyawaty (CV. Ulil Albab Corp, 2024)
The purpose of this study was to determine the influence of government accounting standards, accounting information systems, and internal control systems on the quality of financial reports with human resource competency as a moderator. This research uses quantitative methods and uses primary data. Determining the sample size in this study used a saturated sample. The population in this study was 40 employees, so the sample used was 40 employees. Research hypothesis testing was carried out using the Structural Equation Model (SEM) approach using Smart Partial Least Square (PLS) software version 3.0. The research results show that government accounting standards, accounting information systems, and internal control systems have a significant effect on the quality of financial reports. Government accounting standards and accounting information systems with human resource competence as a moderator have a significant effect on the quality of financial reports. And the internal control system with human resource competence as a moderator does not have a significant effect on the quality of financial reports.